2017
DOI: 10.1534/g3.117.040659
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Genetic Background and Mutational Effects in Regulation of Mouse Craniofacial Shape

Abstract: Inbred genetic background significantly influences the expression of phenotypes associated with known genetic perturbations and can underlie variation in disease severity between individuals with the same mutation. However, the effect of epistatic interactions on the development of complex traits, such as craniofacial morphology, is poorly understood. Here, we investigated the effect of three inbred backgrounds (129X1/SvJ, C57BL/6J, and FVB/NJ) on the expression of craniofacial dysmorphology in mice (Mus muscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 71 publications
0
27
0
Order By: Relevance
“…Their expression is induced upon growth factor stimulation, and the protein products inhibit FGFR‐mediated activation of the ERK‐MAPK signaling pathway . In the mouse, Spry2 and Spry4 prevent the development of supernumerary teeth, and Spry1 , Spry2 , and Spry4 are required for correct molar cusp patterning . In the mouse incisor, which is a continuously growing tooth, Spry2 and Spry4 restrict the differentiation of enamel‐secreting ameloblasts to the labial side, allowing asymmetric enamel deposition …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their expression is induced upon growth factor stimulation, and the protein products inhibit FGFR‐mediated activation of the ERK‐MAPK signaling pathway . In the mouse, Spry2 and Spry4 prevent the development of supernumerary teeth, and Spry1 , Spry2 , and Spry4 are required for correct molar cusp patterning . In the mouse incisor, which is a continuously growing tooth, Spry2 and Spry4 restrict the differentiation of enamel‐secreting ameloblasts to the labial side, allowing asymmetric enamel deposition …”
Section: Introductionmentioning
confidence: 99%
“…(17) In the mouse, Spry2 and Spry4 prevent the development of supernumerary teeth, (7) and Spry1, Spry2, and Spry4 are required for correct molar cusp patterning. (18,19) In the mouse incisor, which is a continuously growing tooth, Spry2 and Spry4 restrict the differentiation of enamel-secreting ameloblasts to the labial side, allowing asymmetric enamel deposition. (20) Here, to further investigate the roles of the FGF signaling pathway in odontogenesis, we utilized a transgenic mouse line (K14-Spry4) in which the expression of mouse Spry4 is driven in the epithelium of many ectodermal organs under the control of the human keratin-14 promoter.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the frequency of craniofacial phenotypes to facilitate future molecular analyses, the Ttc21b aln allele was serially backcrossed onto the C57BL/6J (B6) strain. The B6 genetic background has previously shown to be more susceptible to craniofacial phenotypes in a number of studies (Hide et al 2002;Dixon and Dixon 2004;Mukhopadhyay et al 2012;Percival et al 2017). As the Ttc21b aln was serially backcrossed to the B6 background, we noticed the relative size of the forebrain tissues in B6.Cg-Ttc21b aln/aln mutants increased substantially, although they remained smaller than control brains and still lacked olfactory bulbs ( Fig.1 E,F).…”
Section: Ttc21b Aln Microcephaly Is Background Dependentmentioning
confidence: 51%
“…In particular, the FVB/NJ background was found to be more robust to Sprouty mutations than either 129X1/SvJ or C57BL/6J. This study also revealed that modifier genes can also change the direction of the effect, as the same loss of function mutation in Spry1 caused opposite effects on craniofacial shape in two different inbred backgrounds (Percival et al, ). Finally, pleiotropy modifiers determine the number of features that are affected by a mutation.…”
Section: Variation In Developmental Processesmentioning
confidence: 73%